LEGAL PRINCIPLES OF DEMOCRATIC DOVERNANCE IN UKRAINE - Zvizdai O.V. (Pressing Problems of Public Administration, 2015)
Studied constitutional and legal principles of formation and functioning of local government in Ukraine. Analyzed source base of local government. Solved issues reflected in the key laws of Ukraine concerning local government of the modem concept of local government.